Leprosy Post-Exposure Prophylaxis (LPEP) programme: study protocol for evaluating the feasibility and impact on case detection rates of contact tracing and single dose rifampicin. Issue 11 (17th November 2016) - Barth-Jaeggi, Tanja; Steinmann, Peter; Mieras, Liesbeth; van Brakel, Wim; Richardus, Jan Hendrik; Tiwari, Anuj; Bratschi, Martin; Cavaliero, Arielle; Vander Plaetse, Bart; Mirza, Fareed; Aerts, Ann
Abstract : Introduction: The reported number of new leprosy patients has barely changed in recent years. Thus, additional approaches or modifications to the current standard of passive case detection are needed to interrupt leprosy transmission. Large-scale clinical trials with single dose rifampicin (SDR) given as post-exposure prophylaxis (PEP) to contacts of newly diagnosed patients with leprosy have shown a 50–60% reduction of the risk of developing leprosy over the following 2 years. To accelerate the uptake of this evidence and introduction of PEP into national leprosy programmes, data on the effectiveness, impact and feasibility of contact tracing and PEP for leprosy are required. The leprosy post-exposure prophylaxis (LPEP) programme was designed to obtain those data. Methods and analysis: The LPEP programme evaluates feasibility, effectiveness and impact of PEP with SDR in pilot areas situated in several leprosy endemic countries: India, Indonesia, Myanmar, Nepal, Sri Lanka and Tanzania. Complementary sites are located in Brazil and Cambodia. From 2015 to 2018, contact persons of patients with leprosy are traced, screened for symptoms and assessed for eligibility to receive SDR. The intervention is implemented by the national leprosy programmes, tailored to local conditions and capacities, and relying on available human and material resources. It is coordinated on the ground with the help of the in-country partners of the International Federation of Anti-Leprosy Associations (ILEP). A robust data collection and reporting system is established in the pilot areas with regular monitoring and quality control, contributing to the strengthening of the national surveillance systems to become more action-oriented. Ethics and dissemination: Ethical approval has been obtained from the relevant ethics committees in the countries. Results and lessons learnt from the LPEP programme will be published in peer-reviewed journals and should provide important evidence and guidance for national and global policymakers to strengthen current leprosy elimination strategies.